Earthquake Early Detection Systems: Strategies for Hazard Minimization - Dsouza, Molly (Journal of Research in Science and Engineering, 2025)
Earthquakes are disastrous to mankind. It affects human life, buildings and economy. Overcoming the after effects of earthquakes & diseases all imposes challenges to human life. All these can be minimised if early detection & warning of an earthquake is sent to areas where possibility of occurrence of earthquake is most predominant.